PENGARUH PEMBERIAN EKSTRAK ISOFLAVON TEMPE TERHADAP TINGKAT STRESS OKSIDATIF PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus novergicus) SETELAH DIINDUKSI DENGAN DOSIS TOKSIK PARASETAMOL - Muhamad Taswin; Ratnaningsih Dewi Astuti; Dewi Marlina; Ocktariyana Ocktariyana; Ade Agustianingsih (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2022)
ABSTRACT Background: As a producing country and at the same time the largest consumer of tempeh in the world, Indonesia has become the largest soybean market in Asia. As much as 50% of soybean consumption in Indonesia is done in the form of tempeh. Tempe is a potential food ingredient as a hepatoprotector. The content of isoflavones in tempeh has been shown to protect rat liver function under stress conditions. Isoflavones contained in tempeh have activity as antioxidants, which can prevent oxidation reactions from occurring by working as reducing agents and protecting cell membranes from oxidation, as well as counteracting free radicals by stopping chain reactions and protecting cells from DNA activation so as to reduce cell damage. This situation has prompted the authors to investigate the effect of the isoflavone extract of tempeh on the histochemistry and histopathology of the livers of male white Wistar rats (Rattus novergicus) after being induced by toxic doses of Paracetamol. Methods: This study was an experimental study using the Randomized Posttest Only Control Group Design to determine the level of oxidative stress after administration of tempeh isoflavone extract to male white rats (Rattus novergicus) induced with a toxic dose of paracetamol. 5 groups, namely group 1 was given tempe extract 160 mg/kgBB, group 2 was given tempe extract 320 mg/kgBB, group 3 was given tempe extract 640 mg/kgBB, group 5 was given distilled water and group 6 was given 1% NaCMC solution. Each rat was treated for 14 days. On day 12, 13 and 14 rats were given paracetamol at a dose of 900 mg/kg BW in 1% NaCMC. And on the 15th day, rat blood serum was examined for levels of SGOT, SGPT and MDA. Results: It was found that tempeh at a dose of 640 mg/kgBW could significantly reduce SGOT, SGPT and MDA levels (p<0.05) compared to other doses as well as distilled water and 1% NaCMC. Conclusion: So it can be concluded that tempeh can be an alternative source of antioxidants that can protect liver cells from the effects of substances that can damage the liver. Keywords: Tempe, SGOT, SGPT, MDA